2022
DOI: 10.3348/kjr.2021.0716
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Ultrasound-Guided Radiofrequency Ablation for Primary Hyperparathyroidism: A Prospective Study

Abstract: Objective To assess the efficacy and safety of ultrasound (US)-guided radiofrequency ablation (RFA) in patients with primary hyperparathyroidism (PHPT). Materials and Methods This prospective study enrolled 39 participants (14 male, 25 female; mean age, 59.5 ± 15.3 [range, 18–87] years) between September 1, 2018, and January 31, 2021. All participants had parathyroid lesions causing PHPT, proven biochemically and through imaging. The imaging features of the PHPT nodules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Of 168 unique publications produced from the search query, 17 met the inclusion criteria ( Tables 1,2 ). When more than one study was published from a similar cohort of patients, such as the work by Wei et al ( 16 , 17 ) or the works by Peng et al ( 20 ) and Chai et al ( 21 ), the study with the most number of patients was considered for inclusion in the descriptive statistics. One excluded case study described RFA of an incidental parathyroid gland which was initially misdiagnosed as a thyroid nodule and subsequently needed parathyroidectomy ( 28 ).…”
Section: Methodsmentioning
confidence: 99%
“…Of 168 unique publications produced from the search query, 17 met the inclusion criteria ( Tables 1,2 ). When more than one study was published from a similar cohort of patients, such as the work by Wei et al ( 16 , 17 ) or the works by Peng et al ( 20 ) and Chai et al ( 21 ), the study with the most number of patients was considered for inclusion in the descriptive statistics. One excluded case study described RFA of an incidental parathyroid gland which was initially misdiagnosed as a thyroid nodule and subsequently needed parathyroidectomy ( 28 ).…”
Section: Methodsmentioning
confidence: 99%
“…A prospective study showed that complete ablation was achieved in 38 of the 39 nodules in the 39 enrolled participants in RFA in patients with PHPT. Recurrent laryngeal nerve paralysis occurred in 5.1% of the patients, who recovered spontaneously within three months [ 5 ]. These data indicate that RFA might be an alternative therapy for patients who cannot tolerate undergoing surgery.…”
mentioning
confidence: 99%